Morphological and molecular evidence for a new species of Pseudanisakis Layman & Borovkova, 1926 (Nematoda: Ascaridida), parasitizing Rajiformes in southern Southwest Atlantic waters - Irigoitia, Manuel Marcial; Braicovich, Paola Elizabeth; Farber, Marisa Diana; Timi, Juan Tomás (2018)
Pseudanisakis argentinensis n. sp. is proposed to accommodate parasitic nematodes found in six skate species (Rajidae and Arhynchobatidae) examined from southern Southwest Atlantic waters. The new species differs from its congeners by the following combination of characters: a cupola on each lip, males with 8–12 pairs of precloacal genital papillae, a larger size for both males and females, a greater length-to-breadth ratio of the ventriculus and the presence of a small knob on the tip of the tail. Allometric growth was observed for several morphometric features; however, the slopes of the allometric relationships across host species exhibited non-significant differences and were considered as a strong evidence for conspecificity. Congruent results were obtained after the genetic characterization of the mitochondrial cytochrome c oxidase subunit 1 gene of worms obtained from different skate species, whose values of genetic divergence (1.3) lay within the range of intraspecific variation. Previous records of specimens referred to as Pseudanisakis tricupola in skates from South American waters are regarded as conspecific with P. argentinensis n. sp.